Ekonom i v.d. s kravatom – hrvatsko-švedski lažni prijatelji - Antunović, Goranka (Array, 2014)
Following a brief discussion of the concept of false friends and several typologies presented in literature, the article focuses on Croatian-Swedish false pairs. A broad definition of the term is adopted, which not only recognizes as false friends pairs of etymologically unrelated words, but also considers "false friendship" with regard to the form of the words involved and to their combinatory potential. The first type discussed – false pairs of words whose similar or identical form leads to the incorrect assumption that they share the same meaning – is further divided into three subtypes: pairs of words whose respective meanings differ completely, those whose meanings partly overlap, and those that have the same referential meaning but different pragmatic value. With regard to the second type – false pairs of words whose shared meaning and similar form incorrectly lead to the assumption that the similarity of form is even greater than it actually is – it is pointed out that "false friendship" can apply to the morphological composition and/or to the phonological and orthographic composition of the words. The third type – false pairs of words that share the same meaning but differ in their collocational (combinatory) potential – are shown to be a heterogeneous group that requires further analysis. The article also points out that mistakes in language use can be due not only to false friends in the language pair encompassing a speaker's first language and the language used in a given communicative situation but also to false friends in the language used and another language in the speaker's linguistic repertoire. All the proposed types and subtypes of false friends are illustrated with Croatian-Swedish examples.